Expression of cell cycle proteins in cortical neurons—Correlation with glutamate‐induced neurotoxicity. (4th April 2016) - Negis, Yesim; Karabay, Arzu
Abstract: Under physiological conditions, upon differentiation neurons become irreversibly post‐mitotic by down‐regulating cell cycle progression. However, recent studies have provided evidence that aberrant expression of cell cycle related proteins; especially cyclins, cyclin‐dependent kinases, and their inhibitors are accompanied by programmed cell death in neurons. This abnormal phenotype has been postulated to contribute to the pathophysiology of different neurodegenerative diseases. Glutamate is the most abundant and major excitatory neurotransmitter in the central nervous system but high concentrations are reported to be involved in the pathology of many neurodegenerative diseases. The mechanisms of glutamate neurotoxicity have been intensively investigated over the past decades but still remain not fully understood. In this study, we hypothesized that aberrant regulation of cell cycle proteins may be involved in glutamate‐induced neurotoxicity in primary cultures of rat cortical neurons. The results have shown that, glutamate treatment caused apoptosis by inducing active caspase‐3 and p53 expression. Together with this, an increase in cyclin D1 and Cdk4 protein levels, localization of cyclin D1 to nucleus, and a decrease in the cell cycle inhibitor p27 were observed. After glutamate treatment we also detected up‐regulation of protein kinase C‐α (PKC‐α) protein expression. Altogether, the data reported in this study show for the first time that glutamate in cortical neurons changes simultaneously the expression levels of a number of key cell cycle proteins and cell homeostasis regulators. © 2016 BioFactors, 42(4):358–367, 2016